Influential Factors of Geo-Information Sharing - Basnet, Shanti (Journal on Geoinformatics, Nepal, 2017)
Information resources, spatial or non-spatial are used widely and wisely to improve the organization's operation in today's competitive environment. With the advancement of information and communication technology, information sharing is made feasible and practiced within various entities. However, information sharing can be complex. There are various factors that influence cross-boundary information sharing because each organization operates within complex information, organizational and national context. There can be differences in technology, knowledge, culture, politics, geography, resources, relationships and intentions. This paper highlights on the different factors that can influence the information sharing in different perspectives. Nepalese Journal on Geoinformatics -13, 2014, Page: 7-13